A dynamic method for establishing efficient and scalable rekeying algorithm in mobile WiMAX - Mohd Ali, Borhanuddin; Gilanian Sadeghi, Mohammad Mehdi (2012)
A method of establishing dynamically key management protocol in Mobile WiMAX network is provided, the method includes the steps of dividing into subgroups based on the number of MSs using two tree data structures, wherein the first tree is a special binary tree structure called Set-pruning Tries, and the second tree structure is a B-tree of order 2, applying merging or splitting subgroups based on the existing number of MSs, The binary tree classifies MSs into subgroups by using Connection Identifier (CID) issued by a Base Station (BS).